How are professional football player transfers taxed in South Africa - Nqiwa, Fezile (Department of Commercial Law, 2024)
ABSTRACT In a document entitled Guide on the Taxation of Professional Sports Clubs and Players, the South African Revenue Service (“SARS”) states that it is unlikely that professional soccer clubs could be said to trade in player contracts, and accordingly, player transfers are unlikely to constitute revenue receipts or expenditure as anticipated by the Income Tax Act. The author critically evaluates SARS's assertion by applying the applicable football regulations and well-established South African common-law tax principles to practical scenarios premised upon common player transfer methods, which include combinations of permanent player transfers, temporary player transfers, free player transfers, a bridge player transfer, a buy-out player transfer and buy-back player transfers. The key outcomes and recommendations from this paper are that: I. the commercialisation of football has influenced a change in the player transfer market – clubs are increasingly engaging in speculative player transfer practices. Accordingly, SARS should acknowledge these developments and publish a guideline dedicated to the tax treatment player transfers. II. the Income Tax Act should be amended to include a limited tax exemption on training compensation received by clubs who train young players to become professionals, as the development of young players is social good which should be encouraged and rewarded.